What’s in a name? Defining interdisciplinary learning within and outside the medical realm - Oudenampsen, Jessica; Das, Enny; van de Pol, Marjolein (Research and Humanities in Medical Education, 2022)
Interdisciplinary learning facilitates communication and collaboration with disciplines from outside the medical realm, as is needed in an increasingly complex healthcare system. However, the term ‘interdisciplinary learning’ is often used imprecisely and is often mistaken for interprofessional learning, resulting in terminological and educational confusion. When aware of the definition of both interdisciplinary and interprofessional learning, it is possible to strengthen the potential of both forms of learning. First, the authors propose to reach consensus on the definition of a discipline. When defining the medical discipline without making subdisciplines, it implies that interprofessional learning in healthcare is not necessarily interdisciplinary. Second, the authors elaborate on the specific learning outcomes of interdisciplinary learning. Both interdisciplinary and interprofessional learning focus on ‘boundary crossing’ as a potential key learning outcome. The boundaries crossed however are different. Interdisciplinary learning requires boundary crossing at the level of epistemics and ‘academic cultures’, more so than interprofessional learning.